Local Needs-based Marketing Strategies of Madrasah Aliyah in Rural Areas - Asep Toni Muharam; Mulyawan Safwandy Nugraha; Yoyo Sudaryo; Nunung Ayu Sofiati; Dadan Abdul Aziz Mubarok (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
This study investigates the implementation of local-needs-based marketing strategies at MA Al-Wasilah Lil Hasanah, a Madrasah Aliyah in Warungkiara, Sukabumi, West Java, Indonesia, where educational access is often constrained in rural areas. Employing a qualitative case study approach, data were collected through in-depth interviews, participatory observations, and document analysis. The findings demonstrate that a hybrid marketing model, integrating community-based engagement with digital strategies, significantly enhances student enrollment and community trust. Traditional methods, such as religious gatherings and social events, foster strong local connections, while digital marketing, despite infrastructural challenges, broadens outreach. By aligning strategies with socio-cultural values, the madrasah strengthens its sustainability and public confidence. This research offers practical insights for optimizing marketing in Islamic schools and highlights the potential of hybrid models for global Islamic educational institutions facing similar challenges. Further studies are recommended to explore the long-term efficacy of digital marketing in rural education settings.